THE EFFECT OF HALAL AWARENESS, RELIGIOSITY, PRODUCT INGREDIENTS KNOWLEDGE, AND HALAL CERTIFICATION ON THE PURCHASE DECISION OF HALAL FAST FOOD - Syifana Ghita Santosa; Muhamad Rizky Rizaldy (Faculty of Islamic Economics and Business, 2022)
Introduction: Indonesia has become a country with the largest Muslim population in the world. As a Muslim majority population, it is very important to consume halal products that are in accordance with the Qur'an and Sunnah. But in fact, not all products consumed by Muslims have halal certification. Along with the increasing identity of the Muslim community, the current halal lifestyle has become a trend that is in great demand, including the demand of halal fast food. This study aims to analyze the effect of halal awareness, religiosity, knowledge of product ingredients and halal certification in purchasing decisions of halal fast food products. Methods: The data used is primary data collected by using a questionnaire. The analytical technique used is multiple linear regression using the SPSS version 25 application. Results: This study found that the variables of halal awareness (X₁), religiosity (X2), product material knowledge (X3), and halal certification (X4) significantly influenced the decision to purchase halal fast food by 66%. This research produces a multiple linear regression equation as follow: Y=5.073 + 0.318X₁ + 0.106X₂ + 0.137X₃ + 0.351X₄ + e. Conclusion and suggestion: The implications of this research are given to producers and consumers of fast food to consider the importance of halal certification, which starts from awareness of consuming halal products which are then expected to be committed to their religion. With this research, it is hoped that there will be an increase in halal certification in fast food, especially in Indonesia, one of which is through incessant socialization of the importance of halal certification in fast food. Keywords: Halal Awareness, Religiosity, Knowledge of Product Ingredients, Halal Certification of Fast Food.